Impact of Electron-Beam Irradiation on Functional Attributes of Seeds of Two Coastal Wild Legume Landraces of Canavalia - Supriya, Prabhavathi; Sridhar, Kandikere R.; Ghate, Sudeep D. (Recent Patents on Biotechnology, 2018)
Background: Vegetable proteins have widespread application in the food industry as functional ingredients in food formulations according to the recent patents. Requirement to develop less expensive protein-rich supplementary foods has resulted in shift of emphasis towards lesser known wild than popular legumes. Objective: The aim of this study is to expose seeds of two coastal sand dune wild legumes of the Southwest India (Canavalia cathartica and C. maritima) to different doses of electron-beam (EB) irradiation to assess changes in functional attributes. Method: Intact dried seeds were exposed to EB irradiation (2.5, 5, 10, 15 kGy). Protein solubility, gelation concentration, water-absorption capacity, oil-absorption capacity, emulsion properties and foam properties of control and irradiated seeds were assessed by standard methods. Results: Protein solubility of both seed flours attained the highest at 2.5 kGy, followed by gradual dosedependent decrease. The gelation concentration increased in C. cathartica only at 5 kGy, while it decreased in C. maritima at 2.5 kGy without further change at higher doses. The water-absorption capacity of C. maritima was significantly higher than C. cathartica in control sample, while at 15 kGy C. cathartica showed significantly higher absorption capacity than C. maritima. The oil-absorption capacity was significantly higher in C. maritima than C. cathartica in control as well as all doses of irradiation. Emulsion activity of C. maritima was slightly higher than C. cathartica in control and irradiated samples, while both seeds showed similar emulsion stability in control with significant increase in C. cathartica at 10 kGy and 15 kGy. The foam capacity in both seeds was similar up to 2.5 kGy followed by significant increase in C. maritima at 5 kGy and 10 kGy. The foam stability was significantly higher C. cathartica than C. maritima in control as well as in irradiated samples. The foam capacity was higher in C. maritima than C. cathartica in control and irradiated samples, which showed gradual time-dependent decrease in stability with higher stability at 8 hr in C. cathartica than C. maritima. Conclusion: Improved functional properties (protein solubility, emulsion stability and foam capacity) and decreased gelation concentration in seeds of C. maritima irradiated at 5 kGy is advantageous in the production of functional foods. Even though both species of Canavalia grew on the coastal sand dunes and their seeds were exposed to same doses of radiation, they differed in functional attributes confirm that it is species-specific. Canavalia seeds being rich in proteins, carbohydrates, essential amino acids, essential fatty acids and bioactive components, further studies on the impact of EB irradiation helps in optimization of nutraceutical potential as well as functional attributes for future applications.
Keywords: coastal sand dunes